Assessing perceived and functional health literacy among Cypriot parents - Menikou, Ioanna; Middleton, Nicos; Papastavrou, Evridiki; Nicolaou, Christiana (My University, 2022)
Health literacy (HL) refers to people’s competencies in accessing, understanding, assessing and applying health information to meet demands in healthcare, preventing illness and promoting health. In the case of children, parental HL is important in establishing health-promoting behaviours and better health outcomes.
Keywords: Health literacy; healthcare